2010
DOI: 10.1021/la1042734
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Triggered Smart Drug Release from Multifunctional Core−Shell Capsules One-Step Fabricated by Coaxial Electrospray Method

Abstract: Multifunctional core-shell capsules that triggered release by ultrasound stimulus were one-step fabricated by the coaxial electrospray method. The TiO(2) shell suppressed the initial burst release of the paclitaxel. Fe(3)O(4) and graphene quantum dots inside the oil core functioned successfully for magnetic targeting and fluorescence imaging, respectively. Paclitaxel was trigger released when the dual layer of titania shell cracked under the ultrasound stimulation, and the releasing profile could be controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 34 publications
1
71
0
Order By: Relevance
“…51 By making a careful selection, it was also possible for the polymeric shell to act as a physical support for core-embedded drug. 71 However, the size and internal structure of core-shell particles have to be precisely controlled, since the release kinetics is mainly determined by drug diffusion through the polymeric shell. 37 It was demonstrated that the coaxial dual-capillary electrospray is capable of producing monodisperse drug-loaded particles with high encapsulation efficiency.…”
Section: Coaxial Electrosprayingmentioning
confidence: 99%
See 2 more Smart Citations
“…51 By making a careful selection, it was also possible for the polymeric shell to act as a physical support for core-embedded drug. 71 However, the size and internal structure of core-shell particles have to be precisely controlled, since the release kinetics is mainly determined by drug diffusion through the polymeric shell. 37 It was demonstrated that the coaxial dual-capillary electrospray is capable of producing monodisperse drug-loaded particles with high encapsulation efficiency.…”
Section: Coaxial Electrosprayingmentioning
confidence: 99%
“…These smart delivery systems enable controlled release of drugs as a response to changes in chemical or physical conditions. 71 With the capability of electrospraying in producing inorganic particles, multifunctional paclitaxel-loaded core-shell particles with ultrasoundtriggered release properties were fabricated in a single step. Initial burst release together with paclitaxel release rate was successfully controlled by ultrasound stimulated cracking of the TiO 2 shell.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of drug delivery carriers, the inner cavity of such particles can store large amounts of drugs, and the encapsulating porous shells provides delivery pathway for drug molecules diffusion. The porous shelled drug carriers are also shown to be mechanically more stable than some other drug carriers, such as those made of polymers, which have revealed a naturally burst release behavior (Jing et al 2011). …”
mentioning
confidence: 99%
“…Two types of mechanisms trigger the release from a capsule: an internal stimulus (e.g., changes of pH [4] or ionic strength of the solution [44]) or an external stimulus (e.g., light [46], magnetic or electric field [47,48], or ultrasound irradiation [49]). The microcapsule response may be based on either the intrinsic properties of the shell or the content of the capsule, and it is sensitive to the trigger impact [50,51].…”
mentioning
confidence: 99%